A Case Study on Star Publications (M) Bhd Next Course of Action - Selvanayagam, Karunaharan (1999)
Star Publications (M) Berhad (SPMB) was established in 1971. The organisation had engaged itself in printing and publishing business. An English language daily - The Star was the core business and later the firm ventured into printing and publishing magazines ranging from business to entertainment. SPMB's main source of income was from the sales of The Star, which had grown over the years from a regional product to a national daily. The firm had registered lower after tax profit in 1998 as compared to the previous year, and that had captured the shareholders' attention and sparked worries among them. So, they wanted the matter resolved soonest possible and it was later brought up to the attention of board of d i rectors.